The effect of defects and notches in quasi-static and fatigue loading of Inconel 718 specimens produced by selective laser melting. (August 2020) - Solberg, Klas; Berto, Filippo
Highlights: Notched and unnotched Inconel 718 specimens analysed in the as-built condition. Notch strengthening was observed in static loading and notch weakening in HCF loading. The failure locations were determined by defects in fatigue loading and by notches in static loading. The influence of the as-built surface within a notch geometry was analysed by FEA and TCD. Abstract: Additively manufactured components are likely to contain defects deriving from the manufacturing process. They are also likely to be designed with high geometric complexity (including notches), due to very few design-limitations. In order to understand the influence of these two types of geometric features, we here investigate as-built Inconel 718 specimens produced by selective laser melting under quasi-static and cyclic loading. Notched and unnotched specimens are considered, and the main emphasis is set on the influence of the defects and on how they influence the failure locations at different load levels.